PENINGKATAN PENGETAHUAN PASIEN HIPERTENSI MELALUI EDUKASI GAYA HIDUP SEHAT DI DESA SUMBERSUKO, KABUPATEN MALANG - Siti Rahmawati (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Hypertension is one of the major health problems with an increasing prevalence worldwide. This condition is largely attributed to the lack of public awareness regarding risk factors and preventive measures. Therefore, education is essential to improve community literacy, particularly in relation to the importance of adopting a healthy lifestyle to reduce the risk of hypertension. This study aimed to evaluate the effectiveness of the pocketbook “Hipertensi, Yuk Pahami Penyebabnya!” in enhancing community knowledge. The research employed a quantitative descriptive method with a pre-test and post-test design. The results revealed that the average knowledge score before the educational intervention was at a low-to-moderate level (70%). Following the intervention, there was a significant improvement, with an average understanding score reaching a high level (60% increase). The pocket book, as an educational tool, proved to be an appropriate and easily comprehensible medium for rural communities, and it can serve as a model for promotive interventions.